The World Maritime University—Sasakawa Global Ocean Institute: A New Institute in a Unique University. (3rd July 2019) - Long, Ronan
Abstract: Building capacity in ocean affairs, the law of the sea, and marine scientific research in relation to the needs of developing countries is an integral part of the U. Convention on the Law of the Sea and associated instruments, including the International Maritime Organization (IMO) treaty regime. This article traces the development of capacity-building initiatives at the World Maritime University (WMU) over the past three decades, including the establishment of the WMU–Sasakawa Global Ocean Institute in 2018. The establishment of the new institute should be viewed within the wider context of the extraordinary philanthropy of the Sasakawa Peace Foundation and the Nippon Foundation in building human resource capacity and in supporting advanced academic research on complicated and contentious ocean issues. The article describes the extensive consultation process that informs the research, education, and capacity development agenda of the new institute, including work on the ocean-related goals of the 2030 Agenda for Sustainable Development.